PERANAN BADAN PELAYANAN TERPADU DAN PENANAMAN MODAL (BPTPM) DALAM MEMBENTUK CITRA PELAYANAN PUBLIK KOTA PEKANBARU - Anggraini, Wenny; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Service is core from communication form where every government and privateinstitutions should apply it well to establish a good image. Badan Pelayanan Terpadudan Penanaman Modal (BPTPM) is one of government institutions in runningadministration service for society. That is related with permit and non-permit which ismeant as one of services to help society people for developing their business and also toimprove economic developing area especially in Pekanbaru. In providing services,BPTPM Pekanbaru got an award â€œCitra Pelayanan Primaâ€ by Central Government asBest institutions from all around Indonesia in providing services to the society people.This research has a purpose for knowing role from BPTPM Kota Pekanbaru to supportnational best provide services in society people.In this research, author has used descriptive qualitative method which is extendsituation and also doing analysis based on survey result from the office. Informants inthis research are 2 people officer services from BPTPM, 2 people from BPTPM inproviding permit, and also 3 people which is using providing services in BPTPM. Thisresearch uses frame as reference in case developing to author about role of BPTM inpublic providing services. Based on that case, if BPTPM does services base on reles, soBPTPM could excellent services to society people.This research collects data with observation, interviews, and alsodocumentation. The Result from this research indicates BPTPM Kota Pekanbaru has arole in doing coordination and providing administration in permit and non permit onintegrating manner which have principal coordination, integration, synchronization,simplication, security and certainly of BPTPM in developing image from Government inPekanbaru that easy, quick, secure, transparent, friendly providing and also best publicservices in society. Nevertheless, in fact imaging in society doesnâ€™t like promises fromBPTPM, many people are dissapointed on services especially in simplicity services andfee transparancy for society people. It gives negative images in society people whichproviding services in BPTPM Kota Pekanbaru.Keyword : Role of BPTPM, Imaging in public services, Pekanbaru City